A Retrospective Short-Term Evaluation Using a Polyaxial Plating System in 60 Small Animal Fractures - Mascellino, Haley; Maritato, Karl; Barnhart, Matthew; Kass, Philip (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objective The aim of this study was to retrospectively evaluate the use, complications and outcomes of the Liberty Lock System (LLS) used to repair fractures in dogs and cats.Study Design Medical records (October 2016–June 2019) of dog and cat fractures repaired with the LLS were reviewed. Data reviewed included signalment, fracture classification, complications and radiographic outcome.Results The LLS was used to repair 60 fractures (57 appendicular and 3 axial) in 54 dogs and 6 cats. Mean time to radiographic union was 6 weeks (range: 4–16). Radiographic union was achieved in all 60 fractures with 55/60 healing without recorded complications. Major complications 4/60 and minor complication 1/60 rates were low and no catastrophic complications occurred. The most common major complication was surgical site infection.Conclusion The LLS allowed for successful repair in all 60 cases with a wide variety of fractures. The LLS had a similar complication rate and time to radiographic union to that reported in other veterinary locking plate systems. The LLS is a reliable locking plate system which offers some advantages such as a low-profile plate with the ability to place non-polyaxial to angled polyaxial screws, to treat fractures in dogs and cats.
Keywords: locking plate systems; fracture; implant design; radiograph